Edukasi: Dampak Penggunaan Gadget Pada Anak Di MIM Kupang Karangdowo Klaten - Thomasia Sulistyowati; Yuliani, Feri Catur (LP3M Universitas Putra Bangsa, 2024)
This activity aims to prevent the negative impacts that gadgets can have on children. This activity is important because many children in MIM Kupang Karangdowo, Klaten use gadgets not only to learn but to play. The implementation method for community service uses a socialization approach, namely lectures, dialogue, discussions and problem solving. The results of the implementation of PKM activities with the theme